A Precursory on The Establishment of Illela Towns/ Villages in The Gwadabawa Metropolitan District by Muhammadu Maiturare Marafa - Fatima Abubakar Gidadawa; Yusuf Sarkingobir; Usman Yusuf Gigane (Periodica Journal, 2022)
This paper aimed to discribe selected monumental locations in the old Gwadabawa created by Maiturare Marafa Gwadabawa. Maiturare Marafa Gwadabawa became sultan in 1915-1924, and was the most successful after the invasion of Sokoto Caliphate by the British. The old Gwadabawa Metropolitan District was a land and extensive district, which disgorged Tangaza, Gada, Illela, and Gudu local governments of present Sokoto State, Nigeria. The great Islamic reformer of the 19th century, Shehu Usman Danfodiyo, was brought up, moulded, and taught in Degel of the present Gwadabawa local government, Sokoto State. Ilela region, was part of Gwadabawa, and presently in Illela local government of Sokoto State, Nigeria. The Sokoto Caliphate was established in the 1804 ad the largest in West Africa in the 19th century that remains for about a hundred years, and left important legacies. During the struggle to laid or consolidate this caliphate popularly known as Daukar Usmaniyya, Shehu and his people or descendants had being moving from place to place preaching, teaching, and waging wars wherever necessary just to place the word of Allah on the crest. This had led to impacts on countless aspects of Hausaland. Maitaturare Marafa Gwadabawa was among the indelible and influential descendants of Shehu, who ascribed to his paths in jihad before the coming of Europeans in Hausaland. Maitaturare succeeded in creating Gwadabawa Metropolitan District from the scrap, in tandem with the bid of Shehu and Abubakar Atiku to protect the Caliphate from the Northeastern region towards Konni, with the provisions of fertile and and extensive agriculture, clearing of lands to settle the immigrants and displaced people, protect the citizens against invasion and wild animals and to provide market for the nation among other objectives. The Gwadabawa was to provide cash crops, food crops, animals and other means of livelihood to the entire region and Sokoto at large. Maitaturare vehemently formed Illela major towns with their subterritories. In Illela, places such as Damba, Araba, Gidan Hamma, Darnar Tsolawo, Sabongarin Darna, Garu etc were formed.
Keywords: Sokoto Caliphate; Shehu Usman Danfodiyo; Gwadabawa; Chimmola